1980
DOI: 10.1099/00221287-121-2-365
|View full text |Cite
|
Sign up to set email alerts
|

Immune-enhanced Phagocytosis of Neisseria gonorrhoeae by Macrophages: Characterization of the Major Antigens to which Opsonins are Directed

Abstract: Antisera were prepared in rabbits against whole organisms of colony type 1 Neisseria gonorrhoeae strains F62 and B (from gonococcal urethritis) and 7122 (a strain typical of those associated with disseminated gonococcal infection), and against purified outer membrane components from the same strains including pili and principal outer membrane protein. Antibody levels to pilj, principal outer membrane protein and lipopolysaccharide were determined using a quantitative enzyme-linked immunosorbent assay. Each ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Nevertheless, opsonic antibody may be produced during gonococcal infection (1) or by immunization of rabbits with gonococci (19,27). Moreover, pili are the most effective antigen at adsorbing the opsonic activity of homologous antiserum, and antiserum raised against purified pili is opsonic, indicating the importance of anti-pilus antibodies for opsonization (19). Our studies with monoclonal antibodies confirm this role.…”
Section: Antibody-dependent Complement-mediated Bactericidalsupporting
confidence: 59%
See 3 more Smart Citations
“…Nevertheless, opsonic antibody may be produced during gonococcal infection (1) or by immunization of rabbits with gonococci (19,27). Moreover, pili are the most effective antigen at adsorbing the opsonic activity of homologous antiserum, and antiserum raised against purified pili is opsonic, indicating the importance of anti-pilus antibodies for opsonization (19). Our studies with monoclonal antibodies confirm this role.…”
Section: Antibody-dependent Complement-mediated Bactericidalsupporting
confidence: 59%
“…of individual host defense systems provide a preliminary screen for functional activity, although some caution must be exercised in directly extrapolating from such studies to immunity in natural infection. Previous studies have reported a potential protective effect of polyclonal anti-pilus antibodies in both opsonization and complement-mediated bactericidal killing (19,27,44). One possible complicating factor of such studies is the presence in polyclonal sera of low levels of more effective antibodies directed against other components present in pilus preparations.…”
Section: Antibody-dependent Complement-mediated Bactericidalmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-pilus antisera reduce the adhesion of both piliated gonococci (60) and purified pili (35) to human buccal epithelial cells. Antibodies to pili opsonize pili for phagocytosis by PMN (36) and macrophages (19) and protect tissue culture cells from the cytotoxic effect of challenge with gonococci (67). Anti-pilus monoclonal antibodies also inhibit adhesion, opsonize, and protect against infection (70,71), and immunization with pili can also protect guinea pigs against infection following gonococcal challenge of subcutaneously implanted plastic chambers (24).…”
Section: Prospects For a Pilus Vaccinementioning
confidence: 99%